Teachers' preferences for proximity and the implications for staffing schools: Evidence from Peru - Eleonora Bertoni; Gregory Elacqua; Diana Hincapié; Carolina Méndez; Diana Paredes (Inter-American Development Bank (IDB), 2019)
This paper explores rank-ordered teacher candidates' preferences for public schools in Peru by analyzing the 2015 teacher hiring process. Our analysis shows that, in seeking permanent positions in public schools, candidates appear to search closer to where they attended their Teacher Education Program (TEP) and prefer to work in urban areas. Moreover, candidates seem to prefer schools with higher enrollment, basic services and located in wealthier areas. These preferences vary by candidates' attributes. Proximity from their TEP seems to be particularly important for females, while urbanicity is more relevant for candidates with high scores in the national teacher test and older than 35 years old. When controlling for previous workplace location, TEP locations and urbanicity play a less important role in teacher preferences. Understanding which school characteristics teachers value the most can help us design new policies and modify the existing ones to attract teachers to hard-to-staff schools.
Keywords: H75; I24; J38; N36; 330; Teacher hiring; Teacher preferences; Teacher labor markets; Peru